2015
DOI: 10.1073/pnas.1504172112
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple component networks support working memory in prefrontal cortex

Abstract: Lateral prefrontal cortex (PFC) is regarded as the hub of the brain's working memory (WM) system, but it remains unclear whether WM is supported by a single distributed network or multiple specialized network components in this region. To investigate this problem, we recorded from neurons in PFC while monkeys made delayed eye movements guided by memory or vision. We show that neuronal responses during these tasks map to three anatomically specific modes of persistent activity. The first two modes encode early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
114
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(129 citation statements)
references
References 43 publications
14
114
1
Order By: Relevance
“…A previous experiment (30) reported this trend but did not find a significant effect, perhaps due to a smaller sample size (295 pairs, compared with our 10,535 pairs). A second prediction is that WM maintenance should modify r sc as a function of r signal ; r sc should be lower between neurons with dissimilar tuning than neurons with similar tuning (18,(29)(30)(31)(32)(33). Indeed, we found that the relationship between r sc and r signal changed as predicted during the delay, compared with the fixation and stimulus epochs (Fig.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…A previous experiment (30) reported this trend but did not find a significant effect, perhaps due to a smaller sample size (295 pairs, compared with our 10,535 pairs). A second prediction is that WM maintenance should modify r sc as a function of r signal ; r sc should be lower between neurons with dissimilar tuning than neurons with similar tuning (18,(29)(30)(31)(32)(33). Indeed, we found that the relationship between r sc and r signal changed as predicted during the delay, compared with the fixation and stimulus epochs (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…2A) (P < 0.005 for all epochs, bootstrap test) (Materials and Methods); and r sc varied as a function of tuning similarity, which we quantified as signal correlation between pairs of neurons during the delay epoch (r signal ) (Materials and Methods) (Fig. 2B) (18,(29)(30)(31)(32)(33). Specifically, we found that the median pairwise r sc was consistently larger for similarly tuned neuron pairs (defined as r signal > 0.25) compared with dissimilarly tuned pairs (defined as r signal < −0.25) (P < 0.001 for all epochs, bootstrap test) (Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have shown that the largely heterogeneous activity patterns of individual neurons in monkey (Kobak et al, 2016; Machens et al, 2010; Mante et al, 2013; Markowitz et al, 2015) and rat (Durstewitz et al, 2010) prefrontal cortex, monkey (Churchland et al, 2010b) and rat (Forsberg et al, 2016) V1, rat olfactory cortex (Kobak et al, 2016), rat thalamus (Chapin and Nicolelis, 1999), rat parietal cortex (Raposo et al, 2014), locust olfactory system (Stopfer et al, 2003), aplysia pedal ganglion (Bruno et al, 2015), and perhaps the entire zebrafish brain (Ahrens et al, 2012) can be explained as generated by a small set of latent variables associated with neural modes. In all these studies, neural modes and their time-varying activation helped describe previously unexplained mechanisms of neural function.…”
Section: Neural Manifolds In Non-motor Brain Corticesmentioning
confidence: 99%